2017
DOI: 10.21786/bbrc/10.2/48
|View full text |Cite
|
Sign up to set email alerts
|

Novel fuzzy optimal controller based on STATCOM to damp SSR oscillations in series compensated systems

Abstract: Phenol is a known prejudicial exotoxin and fi nds place in the environment due to intense activity of petrol industry. The aim of this applied-analytical study is to investigate phenol removal from urban drinking water using batch reactor with using powdered eggshell. Various operating variables are tested for their effects on phenol removal; these include pH, contact time, adsorbent doses, initial phenol concentration, reaction kinetics, and powdered eggshell characteristics. Sample of urban drinking water is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…Asgharnia et al (2019), while investigating the effect of pH on phenol removal efficiency, observed higher efficiency for rice husk activated carbon (RHAC) at pH 6 and rice husk carbon (RHC) at pH 5. The result further agrees with the findings reported by Kashi (2017) and Daraei et al (2013) using powdered eggshell.…”
Section: Factors Affecting Adsorption Behaviorssupporting
confidence: 93%
See 3 more Smart Citations
“…Asgharnia et al (2019), while investigating the effect of pH on phenol removal efficiency, observed higher efficiency for rice husk activated carbon (RHAC) at pH 6 and rice husk carbon (RHC) at pH 5. The result further agrees with the findings reported by Kashi (2017) and Daraei et al (2013) using powdered eggshell.…”
Section: Factors Affecting Adsorption Behaviorssupporting
confidence: 93%
“…Observed to follow the trend CS-SiO 2 /CaCO 3 > ESCaCO 3 > RHSiO 2 . Chraibi et al (2016) and Kashi (2017), in a separate study, show Langmuir isotherm describing the adsorption of phenol onto a calcined eggshell. Giraldo & Moreno-Piraján (2014) observed similar findings over activated carbons derived from eggshell particles.…”
Section: Adsorption Isotherms Studymentioning
confidence: 85%
See 2 more Smart Citations
“…The results of the experimental tests performed on an additive self-tuning (ST) control scheme are presented for a static synchronous series compensator that exhibits rapid responses under all conditions [53,54]. A fuzzy optimal controller based on the STATCOM algorithm was used to simulate oscillations in series-compensated transmission systems [55]. The use of STATCOM was utilized by Gyugyi et al [56] to determine the suitable reactive power flow by using a solid-state approach to rebalance the distribution voltages.…”
Section: -Artificial Intelligent Control Of Hvdc Systemmentioning
confidence: 99%